Guest Editors' Introduction: Gender, Business Ethics, and Corporate Social Responsibility: Assessing and Refocusing a Conversation. Issue 4 (3rd October 2017) - Grosser, Kate; Moon, Jeremy; Nelson, Julie A.
ABSTRACT: This article reviews a conversation between business ethicists and feminist scholars begun in the early 1990s and traces the development of that conversation in relation to feminist theory. A bibliographic analysis of the business ethics (BE) and corporate social responsibility (CSR) literatures over a twenty-five-year period elucidates the degree to which gender has been a salient concern, the methodologies adopted, and the ways in which gender has been analyzed (by geography, issue type, and theoretical perspective). Identifying significant limitations to the incorporation of feminist theory in these literatures, we discuss how feminist scholarship relating to behavior (through psychology and related fields), organizations (through feminist organization studies), and economics (through feminist economics) could be integrated. We suggest that a better integration of feminist theory would strengthen BE/CSR research, and point to new research directions and agendas arising from our approach.